Relationship between price competitiveness, tourist arrivals, and tourism receipts in European countries - Radukic, Snezana; Jovanović, Sonja; Petrović-Ranđelović, Marija; Kostić, Zorana; Ilić, Ivana (Serbian Journal of Management, 2023)
The price of goods and services represents an important factor of attracting tourists and improving destination competitiveness. However, a question arises, whether lower prices in tourism contribute to a greater number of tourist arrivals and higher tourism receipts. The purpose of this paper is to analyse a relationship between price competitiveness and tourist arrivals and tourism receipts in European countries. By means of a cluster analysis, the paper examines the homogeneity of European countries in terms of tourism price competitiveness on the basis of the Travel and Tourism Competitiveness Report for 2017. The results of the research showed that European countries are not homogeneous as far as tourism price competitiveness is concerned. Moreover, countries with a lower price competitiveness level attract a greater number of tourists and yield greater tourism receipts in comparison to the countries with a greater price competitiveness level.
Keywords: price competitiveness; tourist arrivals; tourism receipts; cluster analysis; European countries